The family : a Christian perspective on the contemporary home - Balswick, Jack O.; Balswick, Judith K.; Frederick, Thomas V. (Grand Rapids, MI, Baker Academic, 2021)
"A proven, comprehensive resource on Christian family life. Now updated throughout with discussions of recent family-related issues"--
Includes bibliographical references (pages 343-378) and index
Keywords: Families -- Religious life; Marriage -- Religious aspects -- Christianity; Parenting -- Religious aspects -- Christianity